Renal morphological description of brown brocket deer, Mazama gouazoubira, Fisher 1814 (Artiodactyla; cervidae) (Research, Society and Development, 2020)
The brown brocket deer (Mazama gouazoubira) is a deer that lives in South America, particularly in Brazil and nearby countries such as Uruguay and Argentina. This study aimed to describe the topography, morphology, wraps and renal arterial segments of brocket deer. Used two specimens of M. gouazoubira; through dissection, the skin was completely removed and later scored the arteries of animals with stained latex red later the animals were fixed in a formaldehyde solution 10%. Sequentially through a ventral access block was removed from the animal gut and kidneys disjoint this block. The right kidney located at the level of the vertebrae L1-L3 and the left kidney at the level of vertebrae L2-L4 were presented rounded with smooth convex faces without lobation, wrapped sequentially by a thin fibrous capsule, the renal fat and fascia capsule. Medial to each kidney, the adrenal glands were. Renal artery forked in the hilar region in the cranial and caudal artery sectoral and one of these sectoral arteries (cranial and caudal) originated five main segments directed to the ventral region and the dorsal region each kidney, these segments are again bifurcated arterial segments totaling 14. Microscopically the kidneys presented similar organization to that presented by the ruminants with cortical and medullary region with fused lobes. The kidneys brocket deer resemble the kidneys of other ruminants in general, and to carnivores. Thus, its morphology, topography and the renal arterial segments and anatomical and surgical territories of the species studied have been shown to be unique.